Implementasi Metode Weighted Product Menentukan Beasiswa Bidik Misi Stmik Pringsewu - Muhamad Muslihudin; Renita Fitri Andriyanti (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2018)
As the contents of the Law article 76 no.12 Year 2012 on Higher education, STMIK Pringsewu is one of the universities that provide scholarships to outstanding students or underprivileged students such as Bidik Misi scholarship. Shutter Mission is an educational tuition aid for prospective new students are not economically capable but have good academic potential. The goal is to ease the burden of student education expenses. In determining whether or not a student is awarded a scholarship, it is necessary to build a Decision Support System in order to produce more accurate decisions using the Weighted Product method. Researchers use the Weighted Product method because this method is very easy in making decisions. From each student will be judged based on predetermined criteria, then done the ranking process to get the final value then produce the greatest value so will determine the selected alternatives in the research. Based on the test results, the built system can, speed up the selection process and also can reduce the occurrence of errors. This system is built with PHP Programming Language using MySql database. Based on the five students who have been determined then the final result is really worthy of receiving Bidik Misi scholarship is alternative 1 with the largest Vi vector value 0.240202